Simple Current-Mode Squaring and Square-Rooting Circuits: Applications of MO-CCCCTA - Roy, Suvajit; Paul, Tapas Kumar; Pal, Radha Raman (Trends in Sciences, 2021)
This work provides new designs of simple current-mode squaring and square-rooting circuits using multiple-output current controlled current conveyor transconductance amplifier (MO-CCCCTA) as an active building block. Since the proposed circuits need no other external components, they are capable of high-frequency operation and well fitted for IC fabrication. Furthermore, they are insensitive to ambient temperature and their gains can be controlled easily by adjusting the bias currents of MO-CCCCTA. Additionally, the effects of MO-CCCCTA non-idealities on the designed circuits have also been investigated and discussed. Simulation results generated through PSPICE software using TSMC 0.18 µm CMOS process parameters have been presented to justify the theoretical analysis. The static power consumption, bandwidth, and maximum linearity error in dc transfer characteristic measurement for the square-rooting circuit are found to be 0.17 mW, 445.63 MHz and 1.12 %, while for the squaring circuit they are 0.326 mW, 61.15 MHz and 2.38 %, respectively. The application of the reported circuits as a 2-input vector summation circuit has also been included to strengthen the design ideas. HIGHLIGHTS Simple structures of fully integrable current-mode squarers and square-rooters with low component count and lower power dissipation The circuits are insensitive to temperature drift and their gains can be controlled easily by adjusting the bias currents of MO-CCCCTA Bandwidth, static power dissipation, linearity error of square-rooter are 445.63 MHz, 0.17 mW & ≤ 1.12 %; and for the squarer 61.15 MHz, 0.326 mW & 2.38 %, respectively GRAPHICAL ABSTRACT